2007
DOI: 10.1097/01.ta.0000233663.24838.76
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Nailing for Aseptic Nonunion of Femoral Shaft: A Retrospective Cohort Study for Effect of Reaming Size

Abstract: Exchange nailing can be considered the first choice to treat aseptic nonunions of the femoral shaft. The diameter of the new intramedullary nail should be as large as possible to reinforce the mechanical strength of the repair. The osteogenic potential stimulated by the reaming of cancellous bone graft was similar with over-reaming of 1 mm and with over-reaming of 2 mm or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 40 publications
4
29
0
Order By: Relevance
“…Insertion of the interlocking screws using a free hand technique results in jamming of the interlocking screw with the nail and with cortical bone, providing inherent angular stability of the construct [27]. This concept is supported by a study on femoral nonunion where a positive correlation between reaming diameter and nail size of at least 2 mm larger than the primary nail and the fracture union rate was demonstrated by Wu [28]. Additionally, the distribution of axial forces and compression at the nonunion site is very important.…”
Section: Discussionsupporting
confidence: 60%
“…Insertion of the interlocking screws using a free hand technique results in jamming of the interlocking screw with the nail and with cortical bone, providing inherent angular stability of the construct [27]. This concept is supported by a study on femoral nonunion where a positive correlation between reaming diameter and nail size of at least 2 mm larger than the primary nail and the fracture union rate was demonstrated by Wu [28]. Additionally, the distribution of axial forces and compression at the nonunion site is very important.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, it could provide mechanical rigidity and has biologic effects of increasing periosteal blood flow, activating the inflammatory response and various growth factors to stimulate bone formation which helps to heal the nonunion site [34][35][36][37][38]. There are many authors who reported their series of femoral nonunions by using exchanging nail with a healing rate of 53-100% [4][5][6]39,40]. Hierholzer [41] reported a large series of exchange nailing in 72 patients with femoral shaft nonunion with 98% union rate.…”
Section: Discussionmentioning
confidence: 94%
“…There are several different surgical modalities for treating femoral shaft nonunion, including nail dynamization [4,5], nail exchange [6], plate osteosynthesis [7,8], Ilizarov external fixation with or without electrical or ultrasound stimulation [9][10][11][12], autogenous or allogenic bone grafting [13,14], mono-lateral external fixator [15], vascularized bone transfer and distraction osteogenesis [16,17], and other treatment modalities, such as bone morphogenetic proteins (BMPs) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This involves the removal of a previously placed implant and reaming the medullary canal to a larger diameter than previously, ideally by 2 mm. 8 After reaming, a larger diameter intramedullary nail is placed. When initially reported, this treatment resulted in high success rates.…”
Section: Introductionmentioning
confidence: 99%